Design and Implementation of Full-Stack Conference System for Streamlined Administrative Workflows - Pakpahan, Andrew Fernando (Fakultas Ilmu Komputer, Universitas Klabat, 2025)
This study presents the design, implementation, and evaluation of the 11ISC Conference Management System (CMS), a full-stack web application developed to address the fragmented administrative workflows of the 11th International Scholars Conference. Using the Design Science Research methodology, the system was created in response to recurring challenges such as manual registration, accommodation and transportation coordination, and the time-intensive preparation of Letters of Acceptance. The CMS was evaluated through blackbox functional testing covering twelve primary use cases, all of which passed successfully, including participant registration, payment verification, automated LoA generation, QR-based check-in, and accommodation assignment. Administrator feedback indicated substantial process improvements, with the automated LoA module reducing preparation time by up to 90 percent and integrated room and check-in management significantly decreasing errors associated with the previous spreadsheet-based workflow. Deployed during the conference, the system supported more than 220 participants and over 180 paper submissions, providing real-time dashboards and unified data management. The results demonstrate that the CMS enhances efficiency, accuracy, and coordination, offering a practical and replicable solution for academic event management in similar institutional contexts.